Reception and dilution of the Freinets’ philosophical contribution.Case study: Parisian pedagogical activists after 1945 - Riondet, Xavier (Swiss Journal of Educational Research, 2019)
Progressive Education stems from different schools and trends of thought. How have these collectives evolved and lived on over the years? This article focuses on the example of the French Freinet Movement. Examining how the original Freinet principles of the 1930s were received by the Parisian militants of the 1960s, it offers a reasoned analysis of controversies and divergences within the Freinet Movement at the dawn of a new emerging adventure in institutional pedagogy.